AN ANALYSIS OF THE FACTORS THAT INFLUENCES THE PERFORMANCE AGRICULTURAL EXTENSION WORKER IN LANDAK REGENCY - Benny, Marsianus; Suyatno, Adi; Komariyati, Komariyati (Jurnal Sains Mahasiswa Pertanian, 2019)
ABSTRACTThis study aims to determine the performance of extension agents and analyze the influence of Age, Formal Education, Work Experience, Availability of Facilities and Infrastructure, Reward Systems, Distance of Work Areas, and Number of Dominant Commodities of farmers to the performance of extension agents in Landak Regency. This research is included in the type of quantitative research; the location of the study was carried out in Landak Regency by selecting 5 sub-districts which were able to represent the entire population; The method of determining the location is done by purposive method based on certain considerations;Â Methods of collecting data using the survey method. The results of this study can be concluded that the performance of agricultural extension agents in Landak Regency is significantly influenced by formal education, work experience and reward systems. Distance of work area negatively affects the performance of extension agents. While the age variable, the availability of facilities and infrastructure and the number of dominant commodities did not significantly influence the performance of extension agents. Efforts are needed from the government to provide official housing in assisted villages, especially for extension workers whose working area is very far, because it affects the performance of extension workers, in addition close proximity can build intimacy and kinship between farmers and extension agents so as to facilitate all extension activities.Keywords: Extension, Landak Regency, Performance.